2016
DOI: 10.1016/j.chiabu.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of collaborations in sustaining an evidence-based intervention to reduce child neglect

Abstract: Child neglect is the most prevalent form of child maltreatment and represents 79.5% of open child-welfare cases. A recent study found the evidence-based intervention (EBI) SafeCare® (SC) to significantly reduce child neglect recidivism rates. To fully capitalize on the effectiveness of such EBIs, service systems must engage in successful implementation and sustainment; however, little is known regarding what factors influence EBI sustainment. Collaborations among stakeholders are suggested as a means for facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
4
21
1
Order By: Relevance
“…We operationalized sustainment by assessing the extent to which core treatment elements were maintained following the end of the implementation support period and adequate organizational capacity to continue maintenance of these core elements was demonstrated. This definition is consistent with the recommendations from a recent systematic review [8], and this operationalization was also recently employed by Aarons and colleagues [15, 30]. The elements align with the definitions of implementation fidelity (e.g., [31, 32]) in that they included measurement of treatment dose, quality (as measured by staff knowledge, certification, access to high-quality training, and supervision), and penetration (i.e., proportion of staff trained and youth treated in A-CRA).…”
Section: Introductionsupporting
confidence: 76%
“…We operationalized sustainment by assessing the extent to which core treatment elements were maintained following the end of the implementation support period and adequate organizational capacity to continue maintenance of these core elements was demonstrated. This definition is consistent with the recommendations from a recent systematic review [8], and this operationalization was also recently employed by Aarons and colleagues [15, 30]. The elements align with the definitions of implementation fidelity (e.g., [31, 32]) in that they included measurement of treatment dose, quality (as measured by staff knowledge, certification, access to high-quality training, and supervision), and penetration (i.e., proportion of staff trained and youth treated in A-CRA).…”
Section: Introductionsupporting
confidence: 76%
“…These findings are consistent with the studies in behavioral health (i.e., mental health and/or substance use) care settings which have found that multiple factors appear critical to the sustainment of evidence-based practice use [ 21 , 23 25 ]. These studies indicate that a confluence of leadership and staff support are important, along with access to continued resources to maintain the practice under study.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies also suggest that while elements of an evidence-based practice may be sustained, it is typical for some adaptation to occur whereby “partial” rather than “full” sustainment is more likely. For example, Aarons and colleagues [ 15 , 23 ] found that many community-based sites continued to deliver a child neglect intervention following an initial implementation support period showing “operational” sustainment. However, the “structural” elements that help ensure quality delivery, such as ongoing coaching and supervision, were discontinued.…”
Section: Introductionmentioning
confidence: 99%
“…Operationalizing EBT sustainment in this way is consistent with recommendations from a recent systematic review (Wiltsey Stirman et al, 2012) and was recently employed by Aarons and colleagues (Aarons et al, 2016; Green et al, 2015). More specifically, Wiltsey Stirman et al (2012) recommended that the operationalization of program sustainment include the capacity elements needed to function at the required level to maintain program benefit.…”
Section: Introductionsupporting
confidence: 57%